Akar Tradisi Politik Sufi Ulama Kalimantan Barat Abad ke-19 dan 20 - Haris, Didik M Nur; Rahim, Rahimin Affandi Abdul (Universitas Islam Negeri Raden Intan Lampung, 2017)
Politics and Sufism, Two things that would never meet, There is a subjective view that the decline of Islam is due to the Sufis distancing themselves from the social and political activity. Historical facts prove that the Sufis who come to the archipelago have taught the real Islam and comprehensive in both the social, economic and political fields. This review will present historical evidence of the Sufi political tradition in the Indonesian archipelago and West Kalimantan in particular through the study of the third most popular ulamas of West Kalimantan in the 19th and 20th centuries namely AhmadKhatib al-Sambasi (1802-1879), Muhammad Basuni bin Muhammad `Imran (1885-1953) dan Guru Haji Isma’il Mundu (1870 – 1957).